Comparative analysis of hospitalizations among patients treated with hemodialysis and peritoneal dialysis in European pediatric nephrology centers: results from a prospective EPDWG/ESPN Dialysis Working Group study - Bakkaloğlu, Sevcan A; Özdemir Atikel, Yeşim; Schmitt, Claus Peter; Lévai, Eszter; Adalat, Shazia; Goodman, Nadine; Dursun, İsmail; Pınarbaşı, Ayşe Seda; Yazıcıoğlu, Burcu; Paglialonga, Fabio; Vondrak, Karel; Guzzo, Isabella; et al. (Clinical kidney journal, 2024)
BACKGROUND AND HYPOTHESIS: Hospital admissions in pediatric dialysis patients need to be better studied, and most existing studies are retrospective and based on registry data. This study aimed to analyse and compare hospital admission rates, causes, length of stay (LOS), and outcomes in children treated with peritoneal dialysis (PD) and hemodialysis (HD). METHODS: Data from 236 maintenance PD and 138 HD patients across 16 European dialysis centers were collected between 1 July 2017 and 30 June 2018. A total of 178 hospitalized patients (103 PD, 75 HD) were included for further analyses. RESULTS: There were 465 hospitalization events (268 PD, 197 HD) with a rate of 0.39 admissions per 100 patient-days at risk (PDAR) and 2.4 hospital days per 100 PDAR. The admission rates were not significantly different between HD and PD patients. The most common causes of hospitalization were access-related infections (ARI) (17%), non-infectious complications of access (NIAC) (14%), and infections unrelated to access (12%). ARI was the leading cause in PD patients (24%), while NIAC was more common in HD patients (19%). PD patients had more ARIs, diagnostic procedures, and treatment adjustments (P < .05), while HD patients had more NIACs, infections unrelated to access, access placement procedures, and interventional/surgical procedures (P < .001). LOS was longer with acute admissions than non-acute admissions (P < .001). Overall LOS and LOS in the intensive care unit were similar between HD and PD patients. High serum uric acid and low albumin levels were significant predictors of longer LOS (P = .022 and P = .045, respectively). Young age, more significant height deficit, and older age at the start of dialysis were predictors of longer cumulative hospital days (P = .002, P = .001, and P = .031, respectively). CONCLUSION: Access-related complications are the main drivers of hospitalization in pediatric dialysis patients, and growth and nutrition parameters are significant predictors of more extended hospital stays.